2008
DOI: 10.1080/09540260802397446
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Asia

Abstract: Suicide is a major problem worldwide, and suicides in Asian countries account for as much as 60% of all suicides in the world. There are many unique features in suicides within this ethnically-diverse continent, from the methods used, to the putative risk factors. Much research still needs to be done to guide efficacious and culturally relevant interventions in suicide prevention; existing literature suggests a strong focus for programmes that address restricting access to pesticides, increasing crisis counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Additionally, in order to reduce the incidence of death by impulsive suicide, lethal suicide methods, which can be encountered when one feels sudden inclinations to commit suicide, should be less accessible. 3 35 36 37 38 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in order to reduce the incidence of death by impulsive suicide, lethal suicide methods, which can be encountered when one feels sudden inclinations to commit suicide, should be less accessible. 3 35 36 37 38 …”
Section: Discussionmentioning
confidence: 99%
“…The similarity between the profile of people who committed suicide in the selected municipalities and of those in Manaus, with regard to bigger proportions of men and single people, shows nothing out of the expected. Apart from some exceptions, as in some Asian contexts, in which married women commit suicide the most 26 , the preponderance of single men among suicidals is common in almost all the investigated scenarios 25 .…”
Section: Rev Bras Epidemiolmentioning
confidence: 91%
“…Suicide is a leading cause of death among adolescents and young adults and is one of the most pressing public health issues across much of the world. Suicides in Asian countries constitute about 60% of suicides in the world (Wei and Chua) [ 1 ], with Sri Lanka, Japan and South Korea representing the Asian countries having the highest rates of suicide (Hendin et al ) [ 2 ]. By contrast, in the U.S., there is a considerable variation across minority populations with regard to suicide risk (Goldston et al [ 3 ]; Joe, Canetto and Romer [ 4 ]; Walker, Townley and Asiamah [ 5 ]).…”
Section: Perception Of Suicide and Suicide Prevention Messages Formentioning
confidence: 99%
“…A study conducted on hospitalized suicide attempters in Singapore concluded that interpersonal problems were the most common risk factors (Mak, Ho, Chua and Ho [ 33 ]). In China and India, suicide appears to be weakly linked to depression and more strongly linked to acute life stressors (Wei and Chua [ 1 ]). In some South Asian countries with higher rates of suicide, suicides are commonly preceded by family abuse, arguments and conflicts with intimates and in-laws, and unreciprocated love (Chua [ 34 ]; Halliburton [ 35 ]; Marecek [ 25 ]; Widger [ 36 ]).…”
Section: Perceptions Of Mental Illness and Suicide In Asian Culturmentioning
confidence: 99%